Tensile Analysis of Epoxy Resin Composite Material with Petung Bamboo Strip Reinforcement - Bethony, Frans Robert; Pineng, Marthina; Paliling, Formanto; Simon, Christof Geraldi (Politeknik Negeri Ujung Pandang, 2023)
This study aims to analyze the optimal tensile strength of epoxy resin composite material with woven bamboo strips (Dendrocalamus asper). Petung bamboo is made in strips measuring 0.01 cm, 0.1 cm wide, 45 cm long and then woven then soaked in brackish water with variations of soaking for 0, 1, 2, 3, and 4 weeks with river water salinity levels of 10, 20 and 30%. The printed composite material with a composition of 60% epoxy resin and 40% catalyst as a hardener withÂ 1, 2, and 3-layer woven strips and held for 24 hours. Composite material printing by hand lay-up method. For 1 layer of woven composite material, epoxy resin is poured into a mold then woven petung bamboo strip and covered with epoxy resin pressed for 24 hours. The composite material is removed from the molded container and then left in an outdoor airtight room for one week. Composite materials are repaired to ascertain whether there are still defects or no longer exist, especially on the surface of composite materials. The next process is the manufacture of test samples, for tensile tests based on ASTM (D638-02) Before the test is carried out, the sample is repaired first to ensure that the sample is in a standard state to be ready for testing.Â Test results of optimal tensile strength of composite materials with woven reinforcement of petung bamboo strips without immersion of 1 layer (40.22 MPa), 2 layers (50.13 MPa), and 3 layers (60.07 MPa). The optimal tensile strength of composite materials with 1 layer of webbing and soaking time of 3 weeks (51.08 MPa) has increased (19.12%). The optimal tensile strength of composite materials with 2-layer webbing and soaking time of 2 weeks (61.05 MPa) has increased (20.69%). The optimal tensile strength of composite materials with 3-layer webbing and soaking time of 2 weeks (70.15 MPa) has increased (19.08%). Keywords: composite material, bamboo petung, woven strip, brackish water, tensile strength